Effect of the sucrose in the rooting and development “in vitro” of Syngonanthus mucugensis Giul. - Silva, José Roberto dos S.; Lima-Brito, Alone; Santana, José Raniere F. de; Dornelles, Ana Lúcia C. (SITIENTIBUS série Ciências Biológicas, 2005)
The study sought to evaluate the effect of sucrose on the rooting and in vitro development of Syngonantghus mucugensis Giul., endemic plant of Chapada Diamantina/BA. Five different sucrose concentrations were tested in the culture medium MS/2, solidified with 0.8% of agar, and pH adjusted for 5.7 prior to autoclaving. The plant material used consisted of 60 day-old seedlings from the cultivation in vitro with approximately 2 cm in lenght. The seedlings were inoculated in laminar flow in ‘mayonnaise’ type flasks, and mantained in the growth room under photosynthetic active radiation of 9 μmol.m-2.s-1 and temperature of 25 ± 2ºC, for 60 days. The experimental design was entirely randomized with three replicates, in that each consisted of 10 flasks, with inoculated five seedlings per flask. The evaluated parameters were: number of roots, dry weight of the root, total fresh weight and number of leaves produced. The results showed that the sucrose levels had a significant effect on the characteristics analyzed. The reduction of 30 g.L-1 for 15 g.L-1 produced an increment in the number of roots per plant and in the weight of the fresh matter total. The study showed a positive effect of the reduction of the sucrose on the rooting of S. mucugensis, with the concentration of 15 g.L-1 in the culture medium MS/2 bieng the most suitable for the establishment in vitro of this species. Support: IMSEAR/CNPq.